Perilaku Mencari Bantuan Pada Siswa Yang Terindikasi Mengalami Masalah Pertemanan - Hentyan, Desca Anggarica; , Usmi Karyani, S.Psi, M.Si, Psi (2017)
Peer problem is one of problems that often faced by a teenager. If that problem can't be solved well, it might lead to physical violance even depression, moreover will affect the development of adolescents in the future. If someone can't solve the problem by himself/herself, seek for help is the best way to solve it. A survey conducted on 189 students in Muhammadiyah X Junior High School of Surakarta showed that 69% problem that make students angry and feel down is when they're having problems with their friends, such as mocked, teased, quarreling, accused, bullied, and banned. The purpose of this study is to describe help-seeking behavior among students who have peer problems. The researcher used qualitative narrative descriptive approach. Informant of this research were 6 junior high school students consits of 4 boys and 2 girls students who indicated peer problems. Based on screening using the Strengths and Difficulties Questionnaire (SDQ) scale and to collect datas used semi structured interview method. A focus of interview is help-seeking behavior among students who indicated peer problems. The result of this study showed problems that faced by studets at Muhammadiyah X Junior High School of Surakarta were disrupted, dislike by other friends, and quarreled with friends. Part who make problems appear were peers, both school friends or friends' at home. Help-seeking behavior that those students chose were adaptive and executive way, and girls seek more help than boys. Those students' source help were informal such as friends and parents and also semi-formal way like teachers. Therefore friends, parents, and teachers could be guide or protectore for students who has problems. keywords: help-seeking behavior, peer problems, junior high school